Entrer dans la langue ou dans les langues : de la langue maternelle à la langue « mat-rangère » - Monique DE MATTIA-VIVIES (E-REA)
This article reports on a three-year experiment led at the Centre for Early Infancy Socio-Medical Action (CAMSP) at Salvator Hospital in Marseilles. The children accepted for consultations in this facility, accompanied by their parents, all have difficulty speaking and are developmentally delayed in various ways that do not only affect speech. This experiment has its roots in the difficulties encountered by certain University students to assimilate the sounds of English. Confronted with the variable results of traditional approaches to remediating these difficulties, I began to wonder whether they might be rooted in something other than what is for some students an always too brief exposure to the sounds of English. I thought it worth studying how children acquire language, in order to observe whether the difficulties encountered when learning a foreign language are, up to a certain point, of a similar nature to those encountered in one’s own language, when a child starts to speak - or not to.The article leads to theoretical hypotheses concerning the attraction of foreign languages or the resistance they trigger, the elements that facilitate the learning of another language, or that hinder it, in relation to clinical experience.